Can Blended Learning Enhances Student Interest and Understanding in Mathematics? - Jaffar, Ruzaihan (International Journal of Academic Research in Progressive Education and Development, 2020)
Nowadays, the trend of e-learning is increasing day by day and one of the tools to implement this concept is through Blended Learning (BL). Blended learning (face-to-face plus online learning) is now part of the learning landscape in Higher Education, not just for campus-based courses but also for courses designed for students studying at a distance (Distance Education). The higher education or institutions nowadays are trying to run the fully e-learning concept due to space limitation be it in term of storage or in term of locating the students in the classrooms. This paper focuses on exploring blended learning as an approach to the teaching and learning of mathematics in Polytechnics. Its provide insight and understanding of current and future trends regarding how conventional face-to-face instruction in mathematics is influenced by web-based/computer-supported learning. Practical pedagogical issues related to mathematics and blended learning in Higher Education are also discussed. This research aims to identify the problems faced using e-learning which only cover the scope of looking into student interest in learning and look at the research model that is related and show the findings of the appropriate ways of learning. It is hope through the research model identified, it could guide the educators to find the best way of teaching in TVET institutions.